2023
DOI: 10.4041/kjod22.243
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary alveolar bone evaluation following dentoalveolar expansion with clear aligners in adults: A cone-beam computed tomography study

Abstract: Objective To investigate the effects of maxillary orthodontic expansion on the alveolar bone tissue in adult patients treated with aligners by using cone-beam computed tomography. Methods Thirty patients (22 females and 8 males; mean age 36.3 years) were treated with Invisalign ® aligners. Cone-beam computed tomography and digital models were obtained before (T0) and after (T1) upper arch expansion. The bone thicknesses in the cervical, middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The lateral cephalograms reveal the 2-D tooth movement and the airway with defects such as magnification and distortion in the image [ 3 , 4 ]. As for CBCT images, which are now widespread in the clinic for presenting 3-D images of dental-maxillofacial anatomy without image distortion [ 5 7 ], it has been reported that CBCT is capable of evaluating tooth movement through voxel-based superimposition [ 8 11 ]. However, for orthodontists, it violates the principle of as low as reasonably achievable (ALARA) to take CBCT repeatedly in a short period only to evaluate tooth movement.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral cephalograms reveal the 2-D tooth movement and the airway with defects such as magnification and distortion in the image [ 3 , 4 ]. As for CBCT images, which are now widespread in the clinic for presenting 3-D images of dental-maxillofacial anatomy without image distortion [ 5 7 ], it has been reported that CBCT is capable of evaluating tooth movement through voxel-based superimposition [ 8 11 ]. However, for orthodontists, it violates the principle of as low as reasonably achievable (ALARA) to take CBCT repeatedly in a short period only to evaluate tooth movement.…”
Section: Introductionmentioning
confidence: 99%
“…A harmonized relationship between the dentition and underlying basal bone is an important orthodontic treatment goal. 1 , 2 The stability of the boundary of the basal bone before and after orthodontic treatment is critical; thus, teeth moved outside the basal bone boundary during orthodontic treatment can cause severe periodontal and endodontic problems, such as dehiscence, fenestration, 3 and severe root resorption. 4 Therefore, investigating the relationship between the dentition and basal bone is necessary to provide guidelines for the safe movement of teeth during orthodontic treatments in clinical practice.…”
Section: Introductionmentioning
confidence: 99%